Sovereign debt risk in emerging market economies: Does inflation targeting adoption make any difference?. (February 2017) - Balima, Wenéyam Hippolyte; Combes, Jean-Louis; Minea, Alexandru
Highlights: Inflation targeting (IT) adoption improves sovereign debt risk in emerging countries. This favorable effect is sensitive to several structural characteristics. The measure of sovereign risk and the IT form equally influence the effect of IT adoption. IT can improve emerging market economies' access to international financial markets. Abstract: Based on a sample of 38 emerging economies, we find that inflation targeting (IT) adoption improves sovereign debt risk. Next, we show that this favorable effect is sensitive to several structural characteristics, and to the considered time span. Finally, the measure of sovereign risk (sovereign debt ratings or government bond yield spreads) and the IT form (full-fledged or partial) equally influence the effect of IT adoption on sovereign debt risk. Thus, our paper provides valuable insights regarding IT implementation as a device for improving emerging market economies' access to international financial markets.